Structural Insight into Phospholipid Transport by the MlaFEBD Complex from P. aeruginosa. Issue 13 (25th June 2021) - Zhou, Changping; Shi, Huigang; Zhang, Manfeng; Zhou, Lijun; Xiao, Le; Feng, Shasha; Im, Wonpil; Zhou, Min; Zhang, Xinzheng; Huang, Yihua
Graphical abstract: Highlights: High resolution cryo-EM structures of MlaFEBD in apo, ADP-vanadate and AMPPNP bound states. PLs are bound at different locations in MlaFEBD complex. Anterograde lipid transport is ATP-independent. Abstract: The outer membrane (OM) of Gram-negative bacteria, which consists of lipopolysaccharides (LPS) in the outer leaflet and phospholipids (PLs) in the inner leaflet, plays a key role in antibiotic resistance and pathogen virulence. The maintenance of lipid asymmetry (Mla) pathway is known to be involved in PL transport and contributes to the lipid homeostasis of the OM, yet the underlying molecular mechanism and the directionality of PL transport in this pathway remain elusive. Here, we reported the cryo-EM structures of the ATP-binding cassette (ABC) transporter MlaFEBD from P. areuginosa, the core complex in the Mla pathway, in nucleotide-free (apo)-, ADP (ATP + vanadate)- and ATP (AMPPNP)-bound states as well as the structures of MlaFEB from E. coli in apo- and AMPPNP-bound states at a resolution range of 3.4–3.9 Å. The structures show that the MlaFEBD complex contains a total of twelve protein molecules with a stoichiometry of MlaF2 E2 B2 D6, and binds a plethora of PLs at different locations. In contrast to canonical ABC transporters, nucleotide binding fails to trigger significant conformational changes of both MlaFEBD and MlaFEB in the nucleotide-binding and transmembrane domains of the ABC transporter, correlated with their low ATPase activities exhibited in both detergent micelles and lipid nanodiscs. Intriguingly, PLs or detergents appeared to relocate to the membrane-proximal end from the distal end of the hydrophobic tunnel formed by the MlaD hexamer in MlaFEBD upon addition of ATP, indicating that retrograde PL transport might occur in the tunnel in an ATP-dependent manner. Site-specific photocrosslinking experiment confirms that the substrate-binding pocket in the dimeric MlaE and the MlaD hexamer are able to bind PLs in vitro, in line with the notion that MlaFEBD complex functions as a PL transporter.